Social responsible investment: satisfaction, risks and prospects of development - I.M. Vygivska; G.Yu. Khomenko; K.V. Shumylo (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research is devoted to the study of the features and trends of the development of socially responsible investment in Ukraine. The present study shows that under the current conditions of economic development and political situation in different countries, socially responsible investment of various projects and programs of social significance becomes increasingly important and relevant. Today we observe the appearance of the new forms of implementation of socially responsible business activities, among which the impact-investment and financing of socially significant projects on the principles of venture philanthropy are becoming more and more popular. It is determined that IMP involves, firstly, profit making, and secondly, it expects positive social changes, in particular, in support of sustainable agricultural development, ensuring availability of medical services, affordability of housing, development of environmentally friendly technologies. It was found out that the goal of venture philanthropy is primarily to create a social effect, and, eventually, to generate profits that may appear in the process of implementing the project or the activities of the organization. In the vast majority of cases, this type of financing takes place through direct investment or fixed income securities.